Mechanism and application of fibrous proteins in diabetic wound healing: a literature review - Yan, Lilin; Wang, Yuqing; Feng, Jiawei; Ni, Yiming; Zhang, Ting; Cao, Yemin; Zhou, Mingmei; Zhao, Cheng (Frontiers in Endocrinology, 2024)
Diabetic wounds are more complex than normal chronic wounds because of factors such as hypoxia, reduced local angiogenesis, and prolonged inflammation phase. Fibrous proteins, including collagen, fibrin, laminin, fibronectin, elastin etc., possess excellent inherent properties that make them highly advantageous in the area of wound healing. Accumulating evidence suggests that they contribute to the healing process of diabetic wounds by facilitating the repair and remodel of extracellular matrix, stimulating the development of vascular and granulation tissue, and so on. However, there is currently a lack of a comprehensive review of the application of these proteins in diabetes wounds. An overview of fibrous protein characteristics and the alterations linked to diabetic wounds is given in this article's initial section. Next is a summary of the advanced applications of fibrous proteins in the last five years, including acellular dermal matrix, hydrogel, foam, scaffold, and electrospun nanofibrous membrane. These dressings have the ability to actively promote healing in addition to just covering wounds compared to traditional wound dressings like gauze or bandage. Research on fibrous proteins and their role in diabetic wound healing may result in novel therapeutic modalities that lower the incidence of diabetic wounds and thereby enhance the health of diabetic patients.